Stem cell therapy for hereditary breast cancer - Rassi, H. (Цитология и генетика, 2009)
In this study, we report on recent advances on the functions of embryonic, fetal, and adult stem cell progenitors for hereditary breast cancer therapies. Severalmolecular targeting therapies are described by activation and blocking distinct developmental signaling cascade elements, such as BRCA1, EGFR,hedgehog, Wnt/β catenin, and/or Notch pathways, which are frequently upregulated in cancer progenitor cells during the initiation and development of breast cancer. В огляді наведено дані про недавні досягнення використання попередників зародкових, плідних та дорослих стовбурових клітин в терапії за допомогою молекулярного таргентинга шляхом активації та блокування сигнальних каскадних елементів, таких як BRCA1, EGFR, Wnt/β catenin и Notch pathways, які часто регулюються в попередниках ракових клітин під час ініціації та розвитку рака груді. В настоящем исследовании сообщается о недавних достижениях использования предшественников зародышевых, плодных и взрослых стволовых клеток в терапии наследственного рака груди. Описаны варианты терапии с помощью молекулярного таргетинга путем активации и блокирования сигнальных каскадных элементов, таких как BRCA1, EGFR, hedgehog, Wnt/β catenin и Notch pathways, которые часто регулируются в предшественниках раковых клеток в ходе инициации и развития рака груди.